(untitled) (Research, Society and Development, 2022)
The objective of this work was to verify the effect of humic acid application in association with the growth-promoting bacteria Azospirilum brasilense and Bacillus subtilis on seed germination and on the initial development of white sesame seedlings. The research was carried out in the Laboratory of Seed Technology and Matology (LaSeM), at the University of the State of Mato Grosso – Campus de Alta Floresta. The treatments were composed by the combination of doses of 0, 100, 200, 300, 400 and 500 mL 100 kg-1 of commercial product containing humic acid, composed of 18% of humic acid, in addition to treatment with the bacteria Azospirillum brasilense and Bacillus subtilis, in the same doses as humic acid. The variables analyzed were germination percentage, aerial and root length, fresh and dry mass of the roots. Humic acid showed promise in the cultivation of white sesame.